Relation between Dielectric Relaxation and Rheological Properties of Lubricating Greases - Akihito Suzuki (Japanese Society of Tribologists, 2012)
The dielectric spectroscopy method was applied to the investigation of the dynamics of base oil and thickener of lubricating grease. In order to observe the dielectric relaxations both of base oil and thickener, the lubricating grease formed from polyol ester base oil and lithium 12-hydroxy stearate thickener was prepared. Apparent viscosity, dynamic viscoelasticity and creep properties were measured, and the temperature characteristics of these rheological properties were compared to that of dielectric relaxation time. Prepared lubricating grease showed two dielectric relaxation processes. The dielectric relaxation observed in low-frequency and high-frequency regions were attributed to thickener and polyol ester base oil, respectively. The dielectric relaxation time of the high-frequency relaxation exhibited non-Arrhenius-type temperature dependence. This temperature characteristic is similar to that of viscoelastic relaxation time, shift factor obtained from superposition of creep compliance data, and viscosity of polyol ester base oil. On the other hand, the dielectric relaxation time of the low-frequency relaxation showed Arrhenius-type temperature dependence. However, no clear relation was observed between the dielectric relaxation in low-frequency region and the rheological properties measured in this study.